2020
DOI: 10.1002/cam4.2888
|View full text |Cite
|
Sign up to set email alerts
|

Economics of alternative dosing strategies for pembrolizumab and nivolumab at a single academic cancer center

Abstract: Background The FDA initially approved pembrolizumab and nivolumab for doses based on patient weight, but subsequently amended approval to fixed doses. We estimated savings from novel dosing strategies based on real‐world patient data from a single cancer center. Methods We analyzed all outpatient doses of pembrolizumab and nivolumab administered at three infusion centers affiliated with our academic hospital between July 1, 2018 and Oct 31, 2018. We estimated savings from several dosing strategies with and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 34 publications
3
29
0
Order By: Relevance
“…Recent pharmacoeconomic analyses comparing alternative dosing strategies of pembrolizumab (including weight-based dosing) to FDA-approved labels have estimated major cost savings for the health system with a personalized approach. 20,21 Randomized non-inferiority clinical trials designed with Bayesian methods would be the gold-standard for evaluating these extended dosing regimens in an effective and cost-efficient manner. 9,[22][23][24] Alternatively, therapeutic drug monitoring for personalized dosing -as commonly used for antibiotics and immunosuppressive agents -to achieve plasma or serum drug concentrations within a known therapeutic range is another potential strategy that can be employed in prospective studies to minimize financial toxicity from drug and pharmacy costs in this growing population.…”
Section: Discussionmentioning
confidence: 99%
“…Recent pharmacoeconomic analyses comparing alternative dosing strategies of pembrolizumab (including weight-based dosing) to FDA-approved labels have estimated major cost savings for the health system with a personalized approach. 20,21 Randomized non-inferiority clinical trials designed with Bayesian methods would be the gold-standard for evaluating these extended dosing regimens in an effective and cost-efficient manner. 9,[22][23][24] Alternatively, therapeutic drug monitoring for personalized dosing -as commonly used for antibiotics and immunosuppressive agents -to achieve plasma or serum drug concentrations within a known therapeutic range is another potential strategy that can be employed in prospective studies to minimize financial toxicity from drug and pharmacy costs in this growing population.…”
Section: Discussionmentioning
confidence: 99%
“…This is also reflected by the population exposure of fixed doses of pembrolizumab: median exposures relative to mg/kg dosing were –4.6% and +27.1% for 150 and 200 mg fixed dosing, respectively 33 . If a fixed dose of 150 mg pembrolizumab is selected, drug‐related treatment costs are significantly reduced 54,55 …”
Section: Future Solutions To Tailor Tdm Use To Improve Patient Carementioning
confidence: 99%
“…These data suggest that fixed dosing has equivalent efficacy and safety [ 124 ]. But further analysis considering the average weight of cancer patients (75 kg), showed that only 150 mg of pembrolizumab would be actually required [ 125 ]. These FDA PK simulations demonstrated the same exposure between fixed and weight-based dosing, leading to changes in pembrolizumab dosing (200 mg once every three weeks or 400 mg once every six weeks).…”
Section: The Pharmaco-economic Aspects Of Dosing Strategiesmentioning
confidence: 99%